2022
DOI: 10.1093/gigascience/giab088
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and ciliate protozoa are the main rumen microbes associated with methane emissions in dairy cattle

Abstract: Background Mitigating the effects of global warming has become the main challenge for humanity in recent decades. Livestock farming contributes to greenhouse gas emissions, with an important output of methane from enteric fermentation processes, mostly in ruminants. Because ruminal microbiota is directly involved in digestive fermentation processes and methane biosynthesis, understanding the ecological relationships between rumen microorganisms and their active metabolic pathways is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…Regarding the genus Oribacterium , it had a negative coefficient in both the final ANIM-B and the DMI-B models. This aligns with Oribacterium being a potential H 2 sink in the rumen of sheep 33 and its negative association with CH 4 emissions documented in dairy cows 34 . Future research is warranted to explore and verify if Oribacterium has a quantitative relationship with rumen CH 4 production and can be used as a predictor variable or biomarker of CH 4 emissions.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the genus Oribacterium , it had a negative coefficient in both the final ANIM-B and the DMI-B models. This aligns with Oribacterium being a potential H 2 sink in the rumen of sheep 33 and its negative association with CH 4 emissions documented in dairy cows 34 . Future research is warranted to explore and verify if Oribacterium has a quantitative relationship with rumen CH 4 production and can be used as a predictor variable or biomarker of CH 4 emissions.…”
Section: Discussionsupporting
confidence: 83%
“…However, this assumption needs further more investigation. Previous research confirmed that protozoa associated prokaryotes displayed a variety of functions, such as the adaptability of host cells 34 , 46 , nitrogen fixation 47 , methanogenesis 48 , acetogenesis 33 , provide a defense against predators 49 , and provide nutrients to host cells 35 , 46 . Therefore, other scientific methods such as metagenomics and metatranscriptomics analysis are required to further characterization of the prokaryotic communities associated with the eukaryotic population and their composition and roles in the rumen receiving Se supplemented in the diet.…”
Section: Discussionmentioning
confidence: 84%
“…Ciliate protozoa and rumen fungus have been found to be the main rumen microbes associated with methane emissions in dairy cattle [ 79 , 80 ]. Relationships between ruminal archaea and methane emissions are more contradictory, with some authors finding a positive relationship [ 81 ] and others not [ 79 ].…”
Section: Discussionmentioning
confidence: 99%